Analisis Sentimen terhadap Peluang Kerja di Indonesia selama Masa Pandemi COVID-19 dengan Metode Klasifikasi Naive Bayes - Mohammad Aldinugroho Abdullah; Deni Mahdiana (STMIK Budi Darma, 2022)
The impact of the COVID-19 pandemic is very broad, one of which is in the business sector. This has resulted in an impact on job opportunities during the COVID-19 pandemic in Indonesia. This study aims to conduct in-depth learning related to job opportunities in Indonesia during the COVID-19 pandemic using the Naive Bayes model. The data source used comes from Twitter. The results of this study indicate that the largest AUC score falls to the Random Forest model (79.40%), but for more accurate precision falls to the Naive Bayes model (87.88%). In addition, there is a confusion matrix which shows that the Naive Bayes model trial is running well.